An Emerging Role for IQGAP1 in Regulating Protein Traffic - Mahasin Osman (The Scientific World Journal)
IQGAP1, an effector of CDC42p GTPase, is a widely conserved, multifunctional protein that bundles F-actin through its N-terminus and binds microtubules through its C-terminus to modulate the cell architecture. It has emerged as a potential oncogene associated with diverse human cancers. Therefore, IQGAP1 has been heavily investigated; regardless, its precise cellular function remains unclear. Work from yeast suggests that IQGAP1 plays an important role in directed cell growth, which is a conserved feature crucial to morphogenesis, division axis, and body plan determination. New evidence suggests a conserved role for IQGAP1 in protein synthesis and membrane traffic, which may help to explain the diversity of its cellular functions. Membrane traffic mediates infections by intracellular pathogens and a range of degenerative human diseases arise from dysfunctions in intracellular traffic; thus, elucidating the mechanisms of cellular traffic will be important in order to understand the basis of a wide range of inherited and acquired human diseases. Recent evidence suggests that IQGAP1 plays its role in cell growth through regulating the conserved mTOR pathway. The mTOR signaling cascade has been implicated in membrane traffic and is activated in nearly all human cancers, but clinical response to the mTOR-specific inhibitor rapamycin has been disappointing. Thus, understanding the regulators of this pathway will be crucial in order to identify predictors of rapamycin sensitivity. In this review, I discuss emerging evidence that supports a potential role of IQGAP1 in regulating membrane traffic via regulating the mTOR pathway.